Comparison Of BIM And CAD Efficiency In The Planning Phase: A Case Study Of The Construction At PT. Sinar Meadow International Indonesia, Jakarta - Ashar Herrianto; Monica Dewi; Inge Anggitasari; Susilowati Susilowati (Journal of Innovative and Creativity, 2025)
The rapid development of BIM and CAD greatly influences the world of architecture, engineering, and construction (AEC) today, both in the project planning phase, project implementation phase, operational phase, and until demolish. This makes favorite software such as revit and autocad the standard for practitioners and scientists in the AEC world. This study aims to determine the efficiency and effectiveness of using BIM revit and CAD autocad in planning development projects at PT. Sinar Meadow International Indonesia. Such as design speed, clash detection effectiveness, and efficiency and effectiveness in quantity takeoff. This study uses an experimental observation method with analysis of variance. is a test designed to find the relationship between the two variables comparing between research samples. The research instrument is used in collecting primary data between CAD autocad observations and BIM revit.The results of the analysis of the structural, architectural, and mechanical electrical planning drawing experiments explain that the design using BIM revit is 31% faster than using CAD autocad. While in clash detection, revit with interference check tools found 44 cases compared to 3 cases of manual autocad. For quantity take off work, Revit software uses schedule/quantities tools 260% faster than using conventional with AutoCAD software and AutoCAD is 4% cheaper than Revit software..